Earthquake monitoring and alerting system using vibration sensor and IR sensor with IOT / Muhammad Faiz Mokhtar - Mokhtar, Muhammad Faiz (2024)
This project attempts to address the crucial problem of the lack of earthquake detection and alarm systems in Malaysian structures by designing an earthquake monitoring and alerting system using an Arduino Microcontroller. The system can distinguish between seismic activity and changes in infrared radiation generated by people or objects thanks to the integration of vibration sensors and infrared (IR) sensors. The microcontroller plays a crucial part in analyzing the data from the sensors and then starting up several output devices such an LCD display, an LED, and a buzzer. The buzzer's sound warnings, the LED's visual alerts (flashing lights, colour changes), and the LCD's complete earthquake data (including vibration intensity specifics) all work together to create a powerful alerting system. This study's greatest importance comes from its ability to improve Malaysia's earthquake reaction and preparedness measures. Not only can building and occupant safety be greatly increased by putting an earthquake monitoring and alerting system into place, but timely and accurate information can also be shared with pertinent authorities, emergency responders, and the general public. The community's overall resilience and safety are enhanced by this multidimensional strategy, which combines vibration and infrared sensors with a microcontroller-driven warning system to provide a robust and dependable method of detecting and responding to seismic occurrences.